The Revival of American Labor Law - Wilma B. Liebman (Washington University Journal of Law & Policy, 2010)
The author reviews some important events in the history of American labor law, with particular attention on the National Labor Relatoins Board and its evolution. The author then analyzes America's current economic situation and the effect that it is having on the country's labor market. Lastly, the author offers her opinion on the future of American labor law and labor law reform, specifically the Employee Free Choice Act.
Keywords: Labor law reform; Legislative histories; Collective bargaining; Labor unions; United States. National Labor Relations Board; National Labor Relations Act; Labour law